2013
DOI: 10.3174/ajnr.a3763
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Cervical Internal Carotid Artery Stenting in Combination with Intracranial Thrombectomy in Acute Stroke

Abstract: BACKGROUND AND PURPOSE:In past years, thrombectomy has become a widely used procedure in interventional neuroradiology for the treatment of acute intracranial occlusions. However, in 10 -20% of patients, there are additional occlusions or stenotic lesions of the ipsilateral cervical internal carotid artery. The purpose of this study was to evaluate the feasibility of emergency carotid artery stent placement in combination with intracranial thrombectomy and the clinical outcome of the treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
119
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 22 publications
9
119
3
1
Order By: Relevance
“…Several small case series reported promising results when this combined approach was performed. [4][5][6][7][8][9] One of the major concerns in these patients is the risk of postinterventional symptomatic intracranial hemorrhage (sICH), which may be influenced by the mandatory antiplatelet medication of the stent-placement procedure. The reported rate of sICH varies considerably in the literature, ranging from 0% to 20%.…”
mentioning
confidence: 99%
“…Several small case series reported promising results when this combined approach was performed. [4][5][6][7][8][9] One of the major concerns in these patients is the risk of postinterventional symptomatic intracranial hemorrhage (sICH), which may be influenced by the mandatory antiplatelet medication of the stent-placement procedure. The reported rate of sICH varies considerably in the literature, ranging from 0% to 20%.…”
mentioning
confidence: 99%
“…Mechanical thrombectomy of tandem ICAϪMCA occlusions has been described by several authors, including a proximal-to-distal approach with carotid stent placement to re-establish antegrade flow and access to the intracranial circulation for thrombectomy. [9][10][11][12][13][14] Despite this being necessary in acutely occluded or severe atherosclerotic carotid stenoses, acute cervical dissections can usually be traversed with distal-access catheter technology to target distal ELVOs, first with either direct aspiration and/or stent-retriever thrombectomy for rapid cerebral reperfusion. In our experience, the use of proximal balloon-guide catheters was deferred in preference to lower profile and distal-access aspiration catheters with or without stent retrievers to prevent further injury to the cervical carotid wall during thrombectomy.…”
Section: 27mentioning
confidence: 99%
“…Several investigators have demonstrated the feasibility of emergency ICA stenting combined with intracranial thrombectomy for tandem ICA-MCA occlusions with acceptable rates of successful recanalization, complications, and clinical outcomes. [9][10][11][12][13][14] In two of the recent multicenter trials that demonstrated a benefit of endovascular thrombectomy for AIS, carotid artery stent placement was necessary in 8.6%-12.9% of patients. 6,7 Few studies have focused on the endovascular management of spontaneous cervical dissections with or without tandem intracranial ELVOs in the AIS setting, often limited to small sample sizes because most dissections can be managed medically postthrombectomy.…”
mentioning
confidence: 99%
“…15,29 Stampfl et al found that the mean time to reperfusion was 20 minutes longer in the anterograde approach. 29 Lockau et al had similar results, reporting a shorter median time from groin puncture to final reperfusion with the retrograde approach.…”
mentioning
confidence: 99%
“…15,29 Stampfl et al found that the mean time to reperfusion was 20 minutes longer in the anterograde approach. 29 Lockau et al had similar results, reporting a shorter median time from groin puncture to final reperfusion with the retrograde approach. 15 Furthermore, for patients with tandem occlusions, Lockau et al demonstrated good outcome (mRS score of 0-2) in 52.5% of the thrombectomy-first group versus 33.3% in the stent-first group.…”
mentioning
confidence: 99%